Downregulated miR‐187 contributes to the keratinocytes hyperproliferation in psoriasis. Issue 4 (14th September 2018) - Tang, Lipeng; He, Songmin; Zhu, Ying; Feng, Bing; Su, Zuqing; Liu, Bo; Xu, Fangfang; Wang, Xieqi; Liu, Hongying; Li, Chutian; Zhao, Jie; Zheng, Xirun; et al.
Abstract: Psoriasis is a common chronic skin disease characterized by epidermal hyperplasia and inflammation. However, the pathogenesis of psoriasis is multifactorial and is not fully understood. MicroRNAs (miRNAs) represent a promising class of small, noncoding RNA molecules that have a large impact on cellular functions by regulating gene expression. Here we reported that microRNA‐187 (miR‐187), which is one of the most dynamic microRNAs identified in the deep screening miRNAs profile, is downregulated in inflammatory cytokines‐stimulated keratinocytes and psoriatic skins. By luciferase activity assay and gain‐of‐function studies, we showed that miR‐187 inhibits keratinocytes hyperproliferation by targeting CD276. Moreover, overexpression of miR‐187 decreases acanthosis and reduces the disease severity in psoriasis mouse models. Taken together, the results of our study implies miR‐187 as a critical factor in psoriasis pathogenesis, which could be a potent target for psoriasis treatment. Abstract : MicroRNA‐187, which is declined in the inflammatory cytokines‐stimulated keratinocytes and psoriatic skins, can contribute to keratinocytes hyperproliferation by promoting CD276‐STAT3 signaling.